Endogenous ascorbate restrains apoplastic peroxidase activity during sunflower leaf development. (8th October 2012) - Pinedo, M.; Lechner, L.; Creus, C.; Simontacchi, M.; Aguirrezabal, L.
Abstract Several apoplastic enzymes have been implicated in the control of elongation growth of plant cells. Among them, peroxidases contribute to both loosening and stiffening of the cell wall. They appear to be regulated by various mechanisms, including the action of extracellular inhibitors. To obtain evidence of the role of the enzyme–inhibitor interaction during leaf development, the intercellular washing fluids from Helianthus annuus leaves of different ages were isolated using standard methods of vacuum infiltration and centrifugation. Peroxidase activities, assessed using tetramethylbenzidine as substrate, increased during leaf development, reaching a maximum value after the leaves were fully expanded. An inhibitor, chemically characterised as ascorbate, co‐localised with the enzyme in the apoplast. Moreover, there was a strong negative correlation between the action of peroxidase and the micromolar concentration of ascorbate in the apoplastic fluid. The results show that in growing leaves, the in planta ascorbate concentration is able to restrain peroxidase enzyme activity. Then, at the time of growth cessation, the loss of extracellular ascorbate relieves the inhibition on this enzyme that contributes to wall fixation.